CITRA DIRI PEMIMPIN - Aguswan Khotibul Umam (Postgraduate State Islamic Institute (IAIN) Metro, 2013)
Self-image is a concept of an individual himself. It is formed from learning andexperiences that turn into a belief of an individual identity. It is a way of a person seesinside and thinks about himself in this present time. The self-image of leader is a positiveperspective of his existence as a good leader according to his followers’ realisticperspective on him. The dimension of leadership positive self-image must be a realisticpersonal characteristic of a leader, not merely an effort of self-imaging for the time being.A leader should be able to decide on how he will listen to, explain about, see, and judgesomething consistently. The specification of Islamic leader of any level and sector shouldreflect positive self-image of a d leader as a part of worship and jihad fisabilillah for thesake of Alloh.